Prediksi Progres Aktual Proyek Konstruksi pada Tahap Awal Durasi Menggunakan Earned Value Management - Ery Alfred Ibrahim; Mardiaman Mardiaman (Jurnal Talenta Sipil, 2026)
This study is motivated by the limitations of previous research, which has predominantly focused on project performance evaluation during the execution or completion stages, while the capability of Earned Value Management (EVM) to predict project progress in the early phase remains underexplored. The objective of this study is to analyze and predict the actual progress performance of construction projects during the early stage of project duration. The research adopts a quantitative descriptive-analytical approach by utilizing key EVM indicators, namely Planned Value (PV), Earned Value (EV), and Schedule Performance Index (SPI), along with the development of a predictive model based on cumulative average performance (SPI_avg). The study was conducted on three public building construction projects with durations ranging from 52 to 68 weeks, with evaluation points set at 10% to 50% of the total project duration. The results indicate that the accuracy of the prediction model is highly influenced by the stability of SPI values during the early stage. Projects with stable performance produce lower prediction errors (approximately 20–45%), whereas projects with high performance fluctuations exhibit significantly higher errors (greater than 60%). Projects experiencing extreme acceleration in the early phase tend to produce overestimated predictions due to bias in SPI values. This study recommends the use of more adaptive prediction models, as well as the integration of complementary methods such as Earned Schedule, to improve prediction accuracy under fluctuating project conditions.